Front Cover: Asymmetric Catalytic Assembly of Triple‐Columned and Multilayered Chiral Folding Polymers Showing Aggregation‐Induced Emission (AIE) (Chem. Eur. J. 7/2022). Issue 7 (27th January 2022) - Wang, Jia‐Yin; Tang, Yao; Wu, Guan‐Zhao; Zhang, Sai; Rouh, Hossein; Jin, Shengzhou; Xu, Ting; Wang, Yu; Unruh, Daniel; Surowiec, Kazimierz; Ma, Yanzhang; Li, Yunze; et al.
Abstract : Chirality patterns are commonly observed in the universe and in nature, particularly at micro‐ and macrolevels governing the origin of life on earth. Multilayer folding 3D chirality was discovered as a new addition to the chirality family, which is now achieved at a macromolecular level through asymmetric catalytic polymerization. These polymers show conformational flexibility upon pushing and releasing operations providing a variety of molecular energy levels. Therefore, they can have unique photo and electronic properties and it is anticipated that they will have a great impact on chemistry and materials science in the future. More information can be found in the Research Article by G. Li et al. (DOI: 10.1002/chem.202104102 ).